KONSEP DIFERENSIASI DIRI DALAM SISTEM BOWEN: TINJAUAN FILOSOFIS PENDIDIKAN KELUARGA SEBAGAI FONDASI PEMBENTUKAN IDENTITAS ANAK - Nurul Inayah; Nasikhin; Mustopa (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
This research aims to analyze the concept of self-differentiation in Bowen's system philosophically and its implications for family education as the foundation of children's identity formation. Using a qualitative method and literature review approach as well as a philosophical analysis of Bowen's theory, especially regarding self-differentiation that emphasizes the individual's ability to separate cognitive and emotional functions when interacting in the family, this research provides deep insights. The research findings show that a high level of self-differentiation in family members supports the development of a strong and independent child identity, because children can regulate their emotions and thoughts well, and avoid emotional dependence or unhealthy interaction patterns. Therefore, family education that adopts the principle of self-differentiation from Bowen's system can be an important foundation to ensure the formation of a positive child identity, increase emotional and intellectual independence, and reduce conflict within the family. This approach supports the development of more mature and stable individuals in the context of family and society.